2021
DOI: 10.3390/ma14092138
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Piperazin-2-One-Based Structures: Cyclic Imines, Lactams, Aminophosphonates, and Their Derivatives

Abstract: N-Heterocycles are considered as desirable scaffolds for the development of novel lead compounds for anticancer drug research. Among them, phosphorus-containing amino-derivatives play a crucial role. A series of imines and products of their further reactions with P-nucleophiles were obtained starting from vicinal bisamines. Reaction of ethylenediamine and α-carbonyl esters yielded in novel unexpected products, which structures were confirmed by crystallographic measurements. The cytotoxic activity evaluation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ]. It was shown that further functionalization of the hydroxy group has a pivotal impact on the biological activity of the modified α-hydroxy phosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ]. It was shown that further functionalization of the hydroxy group has a pivotal impact on the biological activity of the modified α-hydroxy phosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…α-Aminophosphonates appear to be a very important class of organic compounds because of their potential biological activities [ 1 , 2 , 3 , 4 ]. The distinctive character of bioactive organophosphorus compounds has established their wide applicability in agricultural and medicinal chemistry [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. α-Aminophosphonates ( Figure 1 ) play a crucial role as a platform to design new drugs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are at the center of interest due to their numerous pharmacological possibilities such as anticancer, antiviral, antimicrobial, antioxidant, and antineoplastic [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Coordination compounds containing such derivatives are considered to be a promising class of antineoplastic agent showing cytotoxic activity against different cell lines [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%